Compendium of impact pathways for adaptation of African agriculture - Nowak, Andreea C. (2023)
This document synthesizes key impact pathways for adaptations in agriculture sectors. Recognizing the evolving nature of climate-related risks, it serves a crucial role in assisting practitioners, researchers, and users in navigating the extensive array of possibilities within agricultural adaptation. Given the overwhelming number of potential pathways, this guide aims to lower the entry barrier by providing generic frameworks. These preliminary models serve as starting points, offering users a foundation upon which they can refine and customize their specific pathways to align with unique contexts and goals. The impact pathways presented in this document are not intended to be definitive; instead, they are designed to be modified and iterated upon. By commencing with a basic structure, users can save valuable time and resources, swiftly advancing towards the development of a tailored pathway that captures the intricacies of their adaptation challenges. The customization process involves several iterations required for ensuring that the pathways are fit-to-context. This involves stakeholder validations for grounding pathways in the reality, aligning indicators to accurately measure what is relevant and needed, developing data protocols and systems for tracking, and rigorously testing pathways through data collection and analysis.